คุณภาพชีวิตการทำงานของพยาบาลวิชาชีพในโรงพยาบาลสามจังหวัดชายแดนภาคใต้ - จินตนา นาคพิน (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The purposes of this research were 1) to investigate the levels of quality of working life of professional nurses in hospitals of three southern border provinces 2) to compare the quality of working-life professional nurse by hospital size, age, gender, education, work experienced, salary, religion, location of hometown and present working place, and province of working place .The samples were 335 professional nurses in the hospital of three southern border provinces Thailand. Research instruments was questionnaire with quality of working of professional nurses which consist of 8 elements:1) safety workplace and promoting health 2) adequate and fair compensation 3) Opportunity to develop human capacitity.4) future integration in the work organization 5) social integration 6) constitutionalism in the work organization 7) Work and Total life space 8) The social relevance of work life .The questionnaires which were tested for content validity .93 and reliability.92.Statistical methods used to analyze the data included percentage, mean, standard deviation , t-test and one-way ANOVA The study showed: 1.The professional nurses’ quality of working-life level was in the good level ( =3.55, SD =.28), the working life that relevance to social was at the highest level ( = 4.17,SD =.30), the fair salary and sufficient was at the lowest level ( = 2.93, SD =.59). For highest awareness was the proud of helping people which this was useful up to the country ( = 4.59, SD =.53), the lowest awareness was the special money that gave to people who work in high risk of dangerous area, the money was appropriated and fair if compared to other similarly professional ( = 1.93, SD =. 95). 2. The perception of quality of working life was not different between professional nurse who has different in personal factors and who has not different in personal factors.